Void density investigation of low temperature InP (chip) /Al2O3/Si (wafer) direct bonding - Shang, Ling Ru (2015)
Silicon photonics has attracted extensive research attention due to its advantages of lower single delay and power consumption, higher level of integration and, as a consequence, more diversifiedfunctionalities. However, InP on Si direct wafer bonding, as one of the promising approach to achieve III-V on Si material integration for Si photonics applications, has limited in its bonding performance because of voids formation at the bonding interface. Void density investigation of direct bonding of indium phosphine (InP) on silicon (Si) by aluminum oxide (Al2O3) as intermediate layer is reported. Two approaches to suppress void density have been demonstrated. In first part of the project, void density was shown to decrease with increasing ALD temperature. Bonding surface characteristics as function of Al2O3 ALD temperature was also investigated. It was found that interfacial void density increases with degrading surface characteristics, namely increasing surface roughness and contact angle. Seamless and void-free bonding interface was also observed. In latter part of the project, in-plane outgassing channels were designed, fabricated and studied to suppress void density. Significant void density suppression has been demonstrated, with at most one order of magnitude reduction at channel Spacing-to-width (S/W) ratio of 3.125. It was found that the void density tends to increase with increasing channel spacing, at fixed channel width; and the void density tends to decrease with increasing channel width, at fixed channel spacing. The trend was further verified by showing the average void density decreases with decreasing S/W ratio. The bonded film was shown good bonding quality, by exhibiting uniform and void-free surface, as well as solid suspended film above channels without any collapse. It was learnt that, to further suppress the void density, the S/W ratio of outgassing channel should be kept as low as possible to enhance outgassing efficiency of the channels.